2019
DOI: 10.1002/dac.3959
|View full text |Cite
|
Sign up to set email alerts
|

Bit error probability of the M‐QAM scheme under ημ fading and impulsive noise in a communication system using spatial diversity

Abstract: SummaryThis paper presents a new and exact expression for the bit error probability (BEP) of the square M‐ary quadrature amplitude modulation (M‐QAM) scheme, with the channel under double gated additive white Gaussian noise (G2AWGN) and η‐μ fading in a communication system using the spatial diversity technique. The expression for the BEP is written in terms of the Appell function. The BEP curves are presented under different values of the number of branches of the maximum ratio combining (MRC) receiver, order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Double-gated noise is added to the background Gaussian noise only when both the gating pulses are unitary. In [23], it is shown that by incorporating spatial diversity in a system affected by double-gated noise and η-μ fading, the BER can be reduced significantly. In [24], using MQAM modulation, bit-error-probability (BEP) is calculated for a communication channel subjected to SαS noise and Rayleigh fading.…”
Section: Bit Error Rate (Ber) Analysis Over Different Non-gaussian Noise Modelsmentioning
confidence: 99%
“…Double-gated noise is added to the background Gaussian noise only when both the gating pulses are unitary. In [23], it is shown that by incorporating spatial diversity in a system affected by double-gated noise and η-μ fading, the BER can be reduced significantly. In [24], using MQAM modulation, bit-error-probability (BEP) is calculated for a communication channel subjected to SαS noise and Rayleigh fading.…”
Section: Bit Error Rate (Ber) Analysis Over Different Non-gaussian Noise Modelsmentioning
confidence: 99%
“…Silva et al presented a new and exact expression for the BEP of the square M ‐QAM scheme, with the channel under G 2 AWGN and η ‐ μ fading in a communication system using the spatial diversity technique. The expression determined by the authors is written in terms of the Appell function.…”
Section: Related Workmentioning
confidence: 99%